Accuracy of fine‐needle aspiration and imaging in the preoperative workup of salivary gland mass lesions treated surgically12. (18th September 2012) - Tryggvason, Geir; Gailey, Michael P.; Hulstein, Stephanie L.; Karnell, Lucy H.; Hoffman, Henry T.; Funk, Gerry F.; Jensen, Chris S.; Van Daele, Douglas J.
Abstract: Objectives/Hypothesis: Fine‐needle aspiration (FNA) biopsy and imaging are commonly used in the preoperative assessment of salivary gland mass lesions. The goal of this retrospective study was to clarify the role of FNA and imaging in the workup of salivary gland masses. Study Design: Retrospective cohort study. Methods: A computer search identified patients with an FNA of a salivary gland lesion with subsequent excision during a 10‐year study period. Chart review of study patients was performed, and information on site of lesion, age, gender, radiologic diagnosis, pain in the tumor area, and facial paralysis was recorded and analyzed. Results: There were 543 patients who had an FNA and subsequent histopathology. The majority of the tumors were in the parotid gland (n = 492, 90.9%), followed by submandibular gland (n = 45, 8.3%). The incidence of malignancy across all sites was 29.7%. The mean patient age was 54.1 years, and 54.1% were female. The sensitivity and specificity of FNA were 85.7% and 99.5%, respectively. Positive predictive value (PPV) was 98.6%, and negative predictive value (NPV) was 94.3%. A total of 464 patients had available radiologic studies. For the radiological diagnoses, sensitivity was 81.8% and specificity was 67.3%, whereas PPV and NPV were 52.7% and 89.3%, respectively. Conclusions: FNA is a reliable method of preoperatively assessing both benign and malignant salivary gland lesions. Preoperative imaging has a lower sensitivity and specificity than FNA in differentiating malignant from benign tumors. Older age, pain, and facial paralysis are clinical features independently associated with malignancy. Laryngoscope, 2013